Somatotype and body composition of referees and assistant referees from the CBF - Alberto Inacio da Silva; Cassiano Ricardo Rech (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n2p143 The aim of this study was to determine and compare the somatotype and body composition of principal soccer referees and assistant soccer referees from the state of Paraná in Brazil, all working for the Brazilian Soccer Confederation - (CBF Confederaçao Brasileira de Futebol). Twenty-five referees participated in this study: 12 principal referees (PR) and 13 assistant referees (AR), all male. The variables body mass, height, skinfolds, body girth and bone diameters were collected with the aim of estimating the referees' body composition and determining their somatotypes. Data are presented in the form of descriptive statistics. Comparisons between the PR and AR groups were made using Student's t test for independent samples. The PR referees had a mean age of 38.5 + 5.1 years of age, body mass of 80.9 + 7.61 Kg, mean height of 179 + 3.3 cm and an average percentage of fat of 20.81 + 3.29%. The AR group were significantly younger on average (37.3 + 3.1 years old, p < 0.05). None of the variables body mass (77.2 + 8.2 Kg), height (178.3 + 5.23) or percentage body fat (18.1 + 4.2%) exhibited any statistical differences. As for somatotypes, it was noted that the PR had predominantly endomorphic characteristics (3.9- 3.6-1.7), while the AR were characterized as mesomorphic (3.7-4.1-2.1). Significant differences were observed between the mesomorphic and ectomorphic components when referees and assistant referees were compared. Therefore, refereeing category was not influenced by the morphological profile of the referees who were analyzed.